Motivation and strategies of Malaysian twitch streamers: enhancing live streaming performance - Tan, Sharmaine (2024)
This research delves into the motivations and strategies employed by Malaysian Twitch streamers to elevate their live streaming performance. In this digital age when it comes to live streaming platforms such as Twitch and YouTube, this study investigates the motivations behind Malaysian Twitch streamers or content creators in pursuit of live streaming careers and their improvement in delivering their content creation by having motivational goals. By using the Uses and Gratification Theory, the study aims to uncover the key strategies that assist in improving live streaming performance by conducting an in-depth analysis of Malaysian Twitch streamers. Therefore, this could help Twitch streamers to improve their motivational ways to enhance the live streaming engagement to improve their creative content.